An Ultraweak Variational Method for Parameterized Linear Differential-Algebraic Equations - Beurer, Emil; Feuerle, Moritz; Reich, Niklas; Urban, Karsten (Frontiers in Applied Mathematics and Statistics, 2022)
We investigate an ultraweak variational formulation for (parameterized) linear differential-algebraic equations (DAEs) w.r.t. the time variable which yields an optimally stable system. This is used within a Petrov-Galerkin method to derive a certified detailed discretization which provides an approximate solution in an ultraweak setting as well as for model reduction w.r.t. time in the spirit of the Reduced Basis Method (RBM). A computable sharp error bound is derived. Numerical experiments are presented that show that this method yields a significant reduction and can be combined with well-known system theoretic methods such as Balanced Truncation to reduce the size of the DAE.